2021
DOI: 10.1097/md.0000000000026391
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis of expression of CC and CXC chemokines in children with autism spectrum disorder

Abstract: To investigate the relationship between the expression of CC and CXC chemokines and autism spectrum disorder (ASD). A total of 62 children with ASD (ASD group) and 60 gender- and age-matched normal children (control group) admitted to our hospital from January 2019 to January 2020 were included in the study. Monocyte chemoattractant protein-1 (MCP-1), macrophage inflammatory protein-1α (MIP-1α), macrophage inflammatory protein-1β (MIP-1β), regulated upon activation, normal T-cell expressed and secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In addition, proin ammatory cytokines and chemotactic factors, such as TNF-α, IL-6, MCP-1 and IL-17, are also thought to take part in the disruption of the BBB, giving rise to 'focal encephalitis' in speci c brain areas [38][39][40][41][42]. Many studies have reported notably higher levels of TNF-α, IL-6 and MCP-1 in the periphery of ASD patients and autism-like rodent animal models [32][33][43][44]. The mRNA levels of TNF-, IL-6 and MCP-1 were signi cantly higher in the cortex of newborn BTBR mice than in C57BL/6 mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, proin ammatory cytokines and chemotactic factors, such as TNF-α, IL-6, MCP-1 and IL-17, are also thought to take part in the disruption of the BBB, giving rise to 'focal encephalitis' in speci c brain areas [38][39][40][41][42]. Many studies have reported notably higher levels of TNF-α, IL-6 and MCP-1 in the periphery of ASD patients and autism-like rodent animal models [32][33][43][44]. The mRNA levels of TNF-, IL-6 and MCP-1 were signi cantly higher in the cortex of newborn BTBR mice than in C57BL/6 mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, pro-in ammatory cytokines and chemotactic factors, TNF-α, IL-6, MCP-1 and IL-17 for example, are also considered to take part in the disruption of BBB which have given rise to 'focal encephalitis' in speci c brain areas [38][39][40][41][42]. Ample of studies have reported the notably rising levels of TNF-α, IL-6 and MCP-1 in the periphery of ASDs patients and the autism like rodent animal models [32][33][43][44]. It was identi ed that the mRNA level of TNF-, IL-6 and MCP-1 were signi cantly higher in the cortex of newborn BTBR mice than in C57BL/6 mice as well (Fig.…”
Section: Discussionmentioning
confidence: 99%